Position and Protection of Civil Rights of Unmarried Children in the Relation of Legal System, Religious Norms, and Social Structure in Indonesia - Jamiluddin, Amir; Mujito, Mujito; Evendi, Wakid (Journal of Social Science Studies, 2024)
This paper critically discusses the position of children born out of wedlock in the national family law system by highlighting their legal status and sociological implications through a qualitative literature study based on thematic analysis. Through a review of various primary references on the Marriage Law, the Civil Code, Compilation of Islamic Law, and a number of major court decisions, it presents the normative reality that illegitimate children have only been legally recognized as having a relationship with their mother, unless there is official recognition of the father as made possible after the issuance of Constitutional Court Decision Number 46/PUU-VIII/2010. This study also reveals the significant obstacles faced by children born out of wedlock due to the incompatibility of the national legal system with the religious norms and social values that dominate society. In addition to formal regulations, pressure from social structures and the power of religious interpretation create challenges in accessing rights to identity, inheritance, and social protection at both the public and private levels. This article recommends the need for simplification of administrative procedures, progressive legal reform, and public education interventions to reduce discrimination and strengthen civil protection for children born out of wedlock. The discussion emphasizes that collaboration between the state, social institutions, law enforcement agencies, and community leaders is crucial to achieving an inclusive and fair protection system. This study contributes to the expansion of academic discourse on family law transformation and the formulation of policies that are more sensitive to the protection of children's rights, particularly for children born out of wedlock.